95 DIRECT ORAL FEEDING AFTER A MINIMALLY INVASIVE ESOPHAGECTOMY: A SINGLE-CENTER PROSPECTIVE COHORT STUDY. (14th September 2020) - Fransen, L; Janssen, T; Aarnoudse, M; Nieuwenhuijzen, G; Luyer, M
Abstract:  : A recent randomized controlled trial showed the safety and feasibility of direct oral feeding following a minimally invasive esophagectomy (MIE). However, significant differences were found regarding complication rate between hospitals, potentially influencing the effect of direct oral feeding. This study aimed to investigate the effect of direct oral feeding compared to the standard of care in a center with low anastomotic leakage and overall complication rates following a MIE. Methods: Patients in this single-center prospective cohort study received either direct oral feeding (intervention group) after a MIE with intrathoracic anastomosis or nil-by-mouth for 5 days postoperative and tube feeding (standard of care). Primary outcome was time to functional recovery—defined as adequate pain control with oral analgesics, recovery of mobility, sufficient caloric intake, no intravenous fluid therapy and no signs of active infection—and length of hospital stay. Secondary outcomes included anastomotic leakage, pneumonia, cardiopulmonary complications and other (surgical) complications. Results: Baseline characteristics were similar in the intervention (n = 85) and control (n = 111) group. Median time to functional recovery was respectively 7 versus 9 days in the intervention and control group (p < 0.001). Median length of hospital stay was respectively 8 versus 10 days in the intervention and control group (p < 0.001). Thirty-day postoperative complications were significantly lower in the intervention group (p = 0.037). Anastomotic leakage and pneumonia rates did not differ between the intervention and control group (respectively 11.8% vs. 10.8%, p = 0.834; 27.1% vs. 33.3%, p = 0.651). Chyle leakage only occurred in the control group (18.9%, p < 0.001). All other postoperative complications were similar between groups. Conclusion: Direct oral feeding in a center with a low postoperative complication rate after a MIE results in a reduced time to functional recovery and a shorter length of hospital stay. Importantly, the 30-day postoperative complication rate was significantly lower in patients directly starting oral feeding.